Symbolic Motivation Behind the Branding of “Warung Muslim” as a Religious Identity in Singaraja Bali - Idris, Muhammad; Nur, Irwan; Syahrin, Alif Alfi; Mahir Pradana (IAIN Palangka Raya, 2025)
Muslim stalls serve as a symbol that the stalls sell products following Islamic principles and values. The entity of Muslim stalls in Singaraja has significance for Muslim consumers amidst the dominance of Balinese religious and cultural practices, including culinary culture. The study aimed to analyze the symbolic motivation behind the branding of Warung Muslims (Muslim stalls) in Singaraja, Bali. The approach used qualitative descriptive with a case study method. The study showed that the motives and intentions behind the branding of Muslim stalls in Singaraja are to create an identity, target Muslim consumers, fulfill market needs, and build trust. The significance of the symbolism of the entity of Muslim stalls is seen from the aspects of trust and the creation of halal assurance. The finding confirms that the branding of Muslim stalls serves as an identity strategy that represents religious values and answers the need for halal assurance for the Muslim minority in Singaraja, Bali.